2018
DOI: 10.1016/j.chest.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Proton Pump Inhibitors vs Histamine Type 2 Receptor Blockers for Preventing Clinically Important Gastrointestinal Bleeding During Intensive Care

Abstract: H2Bs were robustly and consistently associated with significantly lower CIGIB risk compared with PPIs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 28 publications
2
34
1
4
Order By: Relevance
“…24–26 Some previous studies have shown conflicting results regarding the efficacy of PPIs and H 2 RAs for stress ulcer prophylaxis. 7 27 In the present study, we found no significant difference in C. difficile infection rates between patients receiving PPIs versus H 2 RAs for stress ulcer prophylaxis. Previous studies showed that stress ulcer medical prophylaxis increased the risk of C. difficile infection, but it remains unclear whether the risk of C. difficile infection differs between patients receiving PPIs versus H 2 RAs.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…24–26 Some previous studies have shown conflicting results regarding the efficacy of PPIs and H 2 RAs for stress ulcer prophylaxis. 7 27 In the present study, we found no significant difference in C. difficile infection rates between patients receiving PPIs versus H 2 RAs for stress ulcer prophylaxis. Previous studies showed that stress ulcer medical prophylaxis increased the risk of C. difficile infection, but it remains unclear whether the risk of C. difficile infection differs between patients receiving PPIs versus H 2 RAs.…”
Section: Discussioncontrasting
confidence: 57%
“… 6 In 2018, a larger observational study showed that PPIs were associated with a higher risk of CIGIB compared with H 2 RAs in critically ill patients. 7 A recent randomised controlled trial showed no difference in CIGIB between PPIs and H 2 RAs 8 ; however, to our knowledge, no previous study has assessed the superiority of PPIs over H 2 RAs in patients receiving ECMO.…”
Section: Purposementioning
confidence: 93%
“…A recent multicenter retrospective study examined the effect of preventing clinically important GI bleeding (CIGIB) with prophylactic PPIs or H2RA among critically ill adults with at least one stress ulcer risk factor in ICU care in US nonfederal hospitals. They found the hazard ratio for CIGIB was two times greater for PPIs patients than for H2RA patients (adjusted HR 1.82 [95% CI, 1.19-2.78]) (Lilly et al, 2018). H2RA administration has been associated with many rare side effects (cardiac arrhythmia; cardiac arrest occurring with rapid infusion (Hinrichsen et al, 1995;Lee et al, 2004); increases in serum creatinine observed with cimetidine; immune-mediated interstitial nephritis; both cholestatic and hepatocellular injury (Fisher and Le Couteur, 2001); CNS side effects including confusion, restlessness, somnolence, agitation, headaches, dizziness, and hallucinations and seizures with prolonged therapy (Cantu and Korek, 1991); and B12 deficiency with long-term H2RA use (Lam et al, 2013); however, many of these adverse effects are rapidly reversible or resolve after withdrawal of the drug (Fisher and Le Couteur, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…16 However, H2RAs may be associated with a lower incidence of Clostridium difficile infections, hospital acquired pneumonia, and ventilator associated pneumonia compared with PPIs. [17][18][19][20] The final modification to the order set was made to facilitate prescribing of lactated ringers over normal saline. Two studies published in the New England Journal of Medicine in 2018 showed the use of balanced crystalloid solutions, such as lactated ringers and plasma-lyte A, in both critically ill and noncritically ill patients, resulted in a significantly lower incidence of major adverse kidney events within 30 days.…”
Section: Background and Significancementioning
confidence: 99%
“…Two studies published in the New England Journal of Medicine in 2018 showed the use of balanced crystalloid solutions, such as lactated ringers and plasma-lyte A, in both critically ill and noncritically ill patients, resulted in a significantly lower incidence of major adverse kidney events within 30 days. 20,21 Furthermore, unlike balanced crystalloid solutions, fluid resuscitation with normal saline has been associated with hyperchloremic metabolic acidosis, which can lead to several adverse effects including renal vasoconstriction, reduced gastric perfusion, and increased release of inflammatory markers. [23][24][25] The IP CC Admit Order Set is primarily used by rotating medical residents admitting patients to the medical intensive care unit (MICU) at our health system's largest institution.…”
Section: Background and Significancementioning
confidence: 99%